(untitled) (Heritage, 2024)
Looking at examples of the suffering of Orthodox Christians starting from the early Christian up to the modern period, the same elements of martyrological causes and circumstances as well as the character of martyr cults and, later, miracle-working of relics can be observed. Based on this, common hagiographic topos were defined: emphasis on physical beauty, perseverance in faith, cruel torture, the way of establishing the cult and the story of miracle-working. The fact that the martyrological context based on theology, defined in the early Christian period, directly refers to the cults of the new martyrs, especially from the area of Kosovo and Metohija, precisely indicates the continuity of martyrdom for the faith. In such a discourse, the examples of the Kosovo-Metohija new martyrs Grigorije Pećki, Vasilije Pekar and Bosiljka Pasjanska represent not only a link but also a confirmation of the New Testament announcement that there will be suffering for Christ until His second coming, which is also proven by the latest examples of the venerable martyrs of Kosovo-Metohija Hariton and Stefan.